2020
DOI: 10.1371/journal.ppat.1008971
|View full text |Cite
|
Sign up to set email alerts
|

Increased phagocytosis in the presence of enhanced M2-like macrophage responses correlates with increased primary and latent HSV-1 infection

Abstract: After HSV-1 infection, macrophages infiltrate early into the cornea, where they play an important role in HSV-1 infection. Macrophages are divided into M1 or M2 groups based on their activation. M1 macrophages are pro-inflammatory, while M2 macrophages are antiinflammatory. Macrophage phenotypes can shift between M1 or M2 in vitro and in vivo following treatment with specific cytokines. In this study we looked at the effect of M2 macrophages on HSV-1 infectivity using mice either lacking M2 (M2-/-) or overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 58 publications
4
38
1
Order By: Relevance
“…This reduced phagocytosis could be due to high dose of virus infection (10 pfu/cell) which may have shot down the host immune response leading to lower phagocytosis. Complementing this study, we previously showed that higher levels of M2 macrophages are associated with higher phagocytosis [14].…”
Section: Plos Pathogenssupporting
confidence: 66%
“…This reduced phagocytosis could be due to high dose of virus infection (10 pfu/cell) which may have shot down the host immune response leading to lower phagocytosis. Complementing this study, we previously showed that higher levels of M2 macrophages are associated with higher phagocytosis [14].…”
Section: Plos Pathogenssupporting
confidence: 66%
“…Fas/FasL deficiency promoted the maturation of M1 macrophages which might explain why gld and lpr mice had a better outcome of the infection. It is known that M1 macrophages are refractory to HSV-1 replication, at least in vitro ( 56 ), while M2 macrophages promote viral replication ( 57 ). Activated microglia can control virus replication in the brain by producing inflammatory cytokines and chemokines such as IL-6, IL- 1β, type I interferons (IFN-I), CXCL-10, CCL2 and CCL5, which our data partly confirm.…”
Section: Discussionmentioning
confidence: 99%
“…These data could be also related to the lower proinflammatory cytokine secretion (TNFα and IL-6) shown in the present study on porcine DAMs. In this sense, we want to highlight that the increased phagocytosis observed in macrophages cultured on pDAM2 could be explained not only by the polarization towards the reparative phenotype of macrophages [ 73 , 74 ] but also by the presence of differentially preserved proteins detected in this pDAM2. Further studies should be addressed in order to explain the relationship of these actin cuffs surrounding C. albicans after macrophage exposure to pDAM2, and the increased phagocytosis previously described.…”
Section: Resultsmentioning
confidence: 99%
“…These data could be also related to the lower proinflammatory cytokine secretion (TNFα and shown in the present study on porcine DAMs. In this sense, we want to highlight that the increased phagocytosis observed in macrophages cultured on pDAM2 could be explained not only by the polarization towards the reparative phenotype of macrophages [73,74] but also by the presence of differentially preserved proteins detected in this pDAM2.…”
Section: Tnfα and Il-6 Production By Raw-2647 Macrophages Cultured On Human Or Porcine Dams After Candida Albicans Interactionmentioning
confidence: 99%